ONTOLOGY OF SCIENCE INTRODUCTION - Karoma, Karoma; Sartika, Anggun; Rexsy Sanjaya, Cencen; Supriyadi, Supriyadi; Zahiq, Moh. (ILJ: Islamic Learning Journal, 2024)
Science also studies various symptoms and events which basically have benefits for human life. The method used in this research is a qualitative descriptive method. Descriptive research is research that aims to describe the position of reason in Islam. The discussion in ontology starts from all aspects of life that can be tested through the human senses, and then dialogues about the basis of existing insight, scientific ways of thinking, and the characteristics of science. The application of ontology in ontological Islamic Learning Management seeks to ensure and observe that insightful knowledge can truly be proven to exist.